Association between periodontal health status and quality of life: a cross-sectional study - Al-Bitar, Kinan M.; Garcia, Jeffrey M.; Han, Shengtong; Guentsch, Arndt (Frontiers in Oral Health, 2024)
Introduction Attachment loss due to periodontal diseases is associated with functional limitations as well as physical pain and psychological discomfort, which may lead to a reduced quality of life. The purpose of this study is to determine if the oral health status, specifically the periodontal status, influences oral health–related quality of life. Materials and methods Survey data were collected in a US dental school clinical setting in a cross-sectional study. Quality of life related to oral health was assessed with the Oral Health Impact Profile-49 (OHIP-49). In addition, DMFT index, periodontal status, and health literacy scores (dental and medical health literacy) were recorded, and the data of n = 97 subjects were statistically analyzed. Results The DMFT index of the study population was 14.98 ± 6.21 (D: 4.72 ± 4.77; M: 3.19 ± 3.46; F: 7.12 ± 4.62). Of the subjects, 44% were identified as periodontitis cases. These periodontitis cases demonstrated significantly higher OHIP-49 scores (66.93 ± 30.72) than subjects without signs of periodontal diseases (NP) (32.40 ± 19.27, p < 0.05). There was also a significant difference between NP patients and patients with gingivitis (66.24 ± 46.12, p < 0.05). It was found that there was a statistically significant difference between Stage 3 (severe) periodontitis and periodontal health (p = 0.003). Pearson correlations were completed, and positive relationships were found with OHIP-49 and DMFT (0.206, p < 0.05), and periodontal risk self-assessment (0.237, p < 0.05). Age [odds ratio (OR) 4.46], smoking (OR 2.67), and the presence of mobile teeth (OR 2.96) are associated with periodontitis. Conclusions Periodontal diseases may negatively impact the oral health–related quality of life. Patients suffering from periodontitis also showed more missing teeth, which might influence function. Age and smoking are associated with a higher prevalence of periodontitis. A good general health literacy was no guarantee for having an adequate oral literacy.